PENGARUH SISTEM PENGENDALIAN INTERNAL PEMERINTAH TERHADAP KUALITAS LAPORAN KEUANGAN PADA PEMERINTAH KABUPATEN ACEH UTARA - STIE Lhokseumawe (JAKTABANGUN: Jurnal Akuntansi dan Pembangunan, 2017)
The purpose of this study is to examine the relationship of the internal control system of government to the quality of the financial statements at the North Aceh district government. The data processing is done with the help of a simple linear equation models with SPSS. it is known that the coefficient of determination (adjusted R-square) of 0.162, meaning that 16.2% of the variation of the magnitude of the quality of financial reports can be explained by the Internal Control Systems. While the remaining 83.8% is explained by other variables outside the research model. There is that the coefficient of the independent variable internal control system (X) is positive, namely 0.553 with significant value-value of 0.000 (<0.05). This means that the first hypothesis which states "Internal control sisstem positive effect. The value of the coefficient of the independent variable internal control system (X) is positive, namely 0.553 with significant value worth 0.000 (<0.05). This means that the first hypothesis which states "The system of internal control positive effect on the quality of financial reports" received. From the results of the analysis showed that the internal control system of positive and significant impact on the quality of financial statements of North Aceh District.